Alternatives to Phosphinooxazoline (t‐BuPHOX) Ligands in the Metal‐Catalyzed Hydrogenation of Minimally Functionalized Olefins and Cyclic β‐Enamides. Issue 16 (25th July 2017) - Biosca, Maria; Magre, Marc; Coll, Mercè; Pàmies, Oscar; Diéguez, Montserrat
Abstract: This study presents a new series of readily accessible iridium‐ and rhodium‐phosphite/oxazoline catalytic systems that can efficiently hydrogenate, for the first time, both minimally functionalized olefins and functionalized olefins (62 examples in total) in high enantioselectivities ( ee s up to >99%) and conversions. The phosphite‐oxazoline ligands, which are readily available in only two synthetic steps, are derived from previous privileged 4‐alkyl‐2‐[2‐(diphenylphosphino)phenyl]‐2‐oxazoline (PHOX) ligands by replacing the phosphine moiety by a biaryl phosphite group and/or the introduction of a methylene spacer between the oxazoline and the phenyl ring. The modular design of the ligands has given us the opportunity not only to overcome the limitations of the iridium‐PHOX catalytic systems in the hydrogenation of minimally functionalized Z ‐olefins and 1, 1‐disubstituted olefins, but also to expand their use to unfunctionalized olefins containing other challenging scaffolds (e.g., exocyclic benzofused and triaryl‐substituted olefins) and also to olefins with poorly coordinative groups (e.g., α, β‐unsaturated lactams, lactones, alkenylboronic esters, etc.) with enantioselectivities typically >95% ee . Moreover, both enantiomers of the hydrogenation product could be obtained by simply changing the configuration of the biaryl phosphite moiety. Remarkably, the new catalytic systems also provided excellent enantioselectivities (up to 99% ee ) in the asymmetric hydrogenation of another challenging class of olefins – the functionalized cyclic β‐enamides. Again, both enantiomers of the reduced amides could be obtained by changing the metal from Ir to Rh. We also demonstrated that environmentally friendly propylene carbonate can be used with no loss of enantioselectivity. Another advantage of the new ligands over the PHOX ligands is that the best ligands are derived from the affordable ( S )‐phenylglycinol rather than from the expensive ( S )‐ tert ‐leucinol. Abstract :